2022
DOI: 10.2106/jbjs.21.01126
|View full text |Cite
|
Sign up to set email alerts
|

Modern External Ring Fixation Versus Internal Fixation for Treatment of Severe Open Tibial Fractures

Abstract: Major Extremity Trauma Research Consortium (METRC)*Background: Modern external ring fixation has been hypothesized to reduce complications requiring hospital readmission compared with internal fixation when treating patients with high-energy open tibial shaft fractures. In this study, the 1-year probability of a major limb complication was compared between external and internal fixation of severe open tibial fractures.Methods: This multicenter randomized clinical trial included patients 18 to 64 years of age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The results of a randomized controlled trial led by the Major Extremity Trauma Research Consortium (METRC) suggest that even in the case of severe open tibial fractures, the routine use of modern external ring fixation for treatment should be avoided. Patients with poor psychological baselines may require timely psychological intervention if negative emotions worsen within the first week following external fixation treatment [ 57 ]. Notably, internal fixation surgery may be a better choice when both internal and external fixation can be performed on a patient with a fragile psychological health status.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a randomized controlled trial led by the Major Extremity Trauma Research Consortium (METRC) suggest that even in the case of severe open tibial fractures, the routine use of modern external ring fixation for treatment should be avoided. Patients with poor psychological baselines may require timely psychological intervention if negative emotions worsen within the first week following external fixation treatment [ 57 ]. Notably, internal fixation surgery may be a better choice when both internal and external fixation can be performed on a patient with a fragile psychological health status.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised controlled trial among adults with Gustilo type IIIA or type IIIB open tibia fractures in 20 trauma centres in the USA showed that external ring fixation had a higher complication rate than did internal fixation (62% vs 44%, respectively). 27 If open tibia fractures were prioritised over other orthopaedic injuries in tertiary hospitals, this decision might cause delayed and non-operative management for other orthopaedic injuries. A detailed cost and implementation feasibility analysis of intramedullary nailing is required to determine whether it is feasible to offer intramedullary nailing for all open tibia fractures in Malawi and in other LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…This risk can be lowered by adding local antibiotics [ 7 ]. The recent “Fixit” study [ 8 ] has shown that internal fixation is equivalent, if not superior, to external fixation in open fracture cases, and has comparable complication rates. Furthermore, the internal device maintains full mechanical support of the bone, should recurrence, reinfection, or metastatic disease incur.…”
Section: Discussionmentioning
confidence: 99%